The Associations between VEGF Gene Polymorphisms and Diabetic Retinopathy Susceptibility: A Meta-Analysis of 11 Case-Control Studies. (28th April 2014) - Han, Liyuan; Zhang, Lina; Xing, Wenhua; Zhuo, Renjie; Lin, XiaLu; Hao, Yanhua; Wu, Qunhong; Zhao, Jinshun
Abstract : Aims . Published data on the associations of VEGF polymorphisms with diabetic retinopathy (DR) susceptibility are inconclusive. A systematic meta-analysis was undertaken to clarify this topic. Methods . Data were collected from the following electronic databases: PubMed, Embase, OVID, Web of Science, Elsevier Science Direct, Excerpta Medica Database (EMBASE), and Cochrane Library with the last report up to January 10, 2014. ORs and 95% CIs were calculated for VEGF–2578C/A (rs699947), –1154G/A (rs1570360), –460T/C (rs833061), −634G>C (rs2010963), and +936C/T (rs3025039) in at least two published studies. Meta-analysis was performed in a fixed/random effect model by using the software STATA 12.0. Results . A total of 11 studies fulfilling the inclusion criteria were included in this meta-analysis. A significant relationship between VEGF+936C/T (rs3025039) polymorphism and DR was found in a recessive model (OR = 3.19, 95% CI = 1.20–8.41, and P ( z ) = 0.01 ) in Asian and overall populations, while a significant association was also found between –460T/C (rs833061) polymorphism and DR risk under a recessive model (OR = 2.12, 95% CI = 1.12–4.01, and P ( z ) = 0.02 ). Conclusions . Our meta-analysis demonstrates that +936C/T (rs3025039) is likely to be associated with susceptibility to DR in Asian populations, and the recessive model of –460T/C (rs833061) is associated with elevated DR susceptibility.